Development of a Cloud Computing Based Management Information System for MSMEs - Andres Villanueva; Carlos Fernandez; Zhang Li (Yayasan Adra Karima Hubbi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are vital for economic growth in many developing countries, including Indonesia. However, these businesses face significant challenges related to management inefficiencies, limited access to resources, and lack of technological adoption. This study aims to develop a cloud-based Management Information System (MIS) specifically tailored for MSMEs. The system is designed to improve operational efficiency, enhance decision-making, and facilitate better management practices for MSMEs in Indonesia. The research utilizes a design and development approach, incorporating both qualitative and quantitative methods. Data was collected through surveys and interviews with MSME owners and managers to identify their needs and challenges. The MIS was then developed using cloud computing technologies and tested with a sample of MSMEs. The cloud-based MIS successfully streamlined key management processes such as inventory tracking, financial management, and customer relationship management. Users reported increased operational efficiency, easier data access, and better decision-making capabilities. The system proved scalable, allowing MSMEs of different sizes and sectors to benefit from the technology. The study concludes that cloud computing-based MIS can significantly improve the management processes of MSMEs, contributing to their growth and sustainability.